Penggunaan Media Gambar Dalam Pembelajaran Membaca Pada Anak Usia 4-6 Tahun Di TK/Paud Al-Ikhlas Sawah Lawe Kecamatam Koto Parik Gadang Diateh Kabupaten Solok Selatan - Eva Fitrianti; Najmi Hayati; Taufik Hidayat (JURNAL ARMADA PENDIDIKAN, 2023)
The appropriate use of instructional media can help teachers deliver learning materials effectively to children aged 4–6 years. One highly effective medium for presenting learning content is picture media. This study aimed to describe and explain how picture media are used to support letter recognition, imitation/pronunciation, and reading letter combinations into syllables in early reading instruction for children aged 4–6 years. The research employed a descriptive qualitative design. The main research instrument was the researcher, supported by interview and observation guides, stationery, and an audio recorder. The data source comprised children aged 4–6 years. Seven children participated: four boys aged 6 years, two girls aged 5 years, and one girl aged 6 years. The data focused on recognizing letter forms and sounds, imitating/pronouncing vowels and consonants, and reading letter combinations into syllables using picture media at TK/PAUD Al-Ikhlas Sawah Lawe, Koto Parik Gadang Diateh Subdistrict, South Solok Regency. Data were collected through observation, interviews, note-taking, and audio recording. The findings indicate that in introducing alphabet letters, children made pronunciation errors with letters such as /m/, /n/, /r/, and /q/. In imitation/pronunciation activities, children still required assistance in pronouncing several vowels and consonants. In reading letter combinations into syllables, children also needed support to read syllables in words such as sepeda (s-e-p-e-d-a), mobil (m-o-b-i-l), buku (b-u-k-u), ember (e-m-b-e-r), and sepatu (s-e-p-a-t-u).